2004
DOI: 10.1152/ajpcell.00250.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and targeting of endogenous Arf1 and Arf6 small GTPases in kidney epithelial cells in situ

Abstract: ADP-ribosylation factors (Arfs) are small GTPases that regulate vesicular trafficking in exo- and endocytotic pathways. As a first step in understanding the role of Arfs in renal physiology, immunocytochemistry and Western blotting were performed to characterize the expression and targeting of Arf1 and Arf6 in epithelial cells in situ. Arf1 and Arf6 were associated with apical membranes and subapical vesicles in proximal tubules, where they colocalized with megalin. Arf1 was also apically expressed in the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…2a-aЉ, b-bЉ; hollow arrows and white arrowheads, respectively). A partial co-localization of prominin-2 and calbindin-D28k, a calcium-binding protein enriched in connecting tubules (Kojima et al 2002;El-Annan et al 2004), was also observed suggesting the presence of prominin-2 in the distal-most segment of the nephron (Fig. 1e; hollow arrows and white arrowheads, respectively).…”
Section: Localization Of Human Prominin-2 Protein and Transcript In Tmentioning
confidence: 85%
“…2a-aЉ, b-bЉ; hollow arrows and white arrowheads, respectively). A partial co-localization of prominin-2 and calbindin-D28k, a calcium-binding protein enriched in connecting tubules (Kojima et al 2002;El-Annan et al 2004), was also observed suggesting the presence of prominin-2 in the distal-most segment of the nephron (Fig. 1e; hollow arrows and white arrowheads, respectively).…”
Section: Localization Of Human Prominin-2 Protein and Transcript In Tmentioning
confidence: 85%
“…Hence renal PT CdMT uptake and cell death are mediated, at least in part, by megalin and cubilin. The significance of megalin/cubilin mediated RME for CdMT toxicity in PT cells was further confirmed by investigating the role of the small GTPase ARF6 (ADP-ribosylation factor 6), which is involved in internalization of ligands by RME and endocytic vesicular trafficking in rat PT cells (Maranda et al 2001;El-Annan et al 2004). Transfection of a dominant-negative form of ARF6 prevented recycling of megalin to the cell surface.…”
Section: Megalin and Cubilinmentioning
confidence: 87%
“…Arfs are participating in the formation of coated transport vesicles. El-Annan et al have shown abundant expression of Arf1 and Arf6 in the distal nephron and the collecting duct and have demonstrated that Arf1 is mostly localized to the apical membrane whereas Arf6 appeared to be mainly expressed at the basolateral membrane [43]. Arf6 was further demonstrated as a factor promoting Avpr2 recycling [44].…”
Section: Small Gtp-binding Proteinsmentioning
confidence: 99%